Postoperative Results in the Treatment of Retinal Detachment with Scleral Buckling Surgery - Neuhaus, Caroline; Valmaggia, Christophe (Klinische Monatsblätter für Augenheilkunde, 2023)
Background The course after scleral buckling surgery is investigated in patients with rhegmatogenous retinal detachment.Patients and Methods The Ethics Committee of Eastern Switzerland approved the retrospective single-center study (EKOS19/152, Project ID: 2019-02034). The primary endpoint is the anatomical reattachment of the retina 3 months after surgery. Secondary endpoints are visual acuity and the occurrence of intra- and postoperative complications. The patient files of all patients treated for rhegmatogenous retinal detachment with scleral buckling surgery between January 2005 and December 2014 at the Cantonal Hospital of St. Gallen were included.Results In 165 of 184 patients (89.7%), reattachment of the retina 3 months postoperatively was achieved by single scleral buckling surgery. Treatment of rhegmatogenous retinal detachment improved patientsʼ visual acuity by an average of 4.8 ETDRS letters. Intraoperatively, subretinal hemorrhage occurred in one patient. Postoperatively, interfering buckling material was removed in 24 patients (13.1%). A pars plana vitrectomy was performed in six patients (3.2%) due to epiretinal membrane, in two patients (1.1%) due to a macular hole, and in three patients (1.6%) due to disturbing vitreous opacities.Conclusions Scleral buckling surgery is an effective and relatively low complication method for the treatment of selected patients with rhegmatogenous retinal detachment.
Keywords: scleral buckling; retinal detachment; pars plana vitrectomy